Smart Wearable Band for Proactive Bovine Health and Breeding Cycle Monitoring - J., Rohini; S., Praveen; K., Ruthik; S., Nivitha Devi (Journal of ISMAC, 2025)
The Smart Wearable Band for Proactive Bovine Health and Breeding Cycle Monitoring is an IoT-based device. It is designed to address the major issues in cow health and its breeding cycle tracking. Traditional methods for livestock monitoring are manual. They’re slow and can cause errors. Manual observation of the breeding cycle is especially prone to mistakes. It also causes unnecessary pain to the cows. To address all the above mentioned issues, a flexible, wearable health band that can be attached to the tail of the cow is proposed in the study. It’s comfortable and avoids the need for manual observation. The band tracks vital signs like body temperature, heart rate, humidity, and activity levels. If there are any abnormalities seen, it sends an SMS alert to the farmer immediately. This lets farmers take quick action to prevent health issues. The device also helps to monitor and predict the cow’s breeding cycle. It makes breeding timing more accurate and less stressful for the cow. Early diagnosis shows a drop in disease caused and better milk production. The Bovine Health Plus Band is a cost-effective and efficient smart livestock management system.